A prospective randomized comparative study of Misoprostol and balloon tamponade using condom catheter to prevent postpartum hemorrhage at M. Y. H., Indore, India in vaginal delivered patients - Yadav, Sumitra; Malhotra, Anjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: PPH is responsible for quarter of maternal deaths occurring worldwide and its incidence is increasing in developed world. According to Confidential Enquiries into Maternal and Child Health (CEMACH) report obstetric hemorrhage occurs in around3.7 per 1000 births. The objective of the study is that it was a prospective randomized comparative study of misoprostol and balloon tamponade via condom catheter to prevent postpartum hemorrhage in normal delivered patients at MYH. Methods: A sample size of 200 normal delivered patients between age group 18 and 45 years is chosen with excessive bleeding after third stage of labour and after administration of oxytocics. These 200 patients are divided into two groups: First group receiving Misoprostol and applying condom catheter in other group. Both groups are evaluated for PPH. Results: It was found that CG balloon condom catheter was a much better and more effective alternative in controlling PPH than Misoprostol as the failure rate with CG balloon condom catheter were much less than that with misoprostol. Due to its cost effectiveness and being easily available at primary health center and due to absence of any drug reactions and easy technique of formation makes it a better modality in controlling PPH even at PHC. Conclusions: Patients with condom catheter in situ must show better result than patients receiving misoprostol.